Psychological and social impacts of Covid-19 on students’ lives and their adaptive behaviors - Artur Marecos Parreira; Pestana, M.H.; Brandão, M.R. (Internet and Higher Education, 2021)
This article investigates the impact of the pandemic on Brazilian and Portuguese students from technical and university schools. A study by questionnaire, complemented by qualitative interpretation of data, was carried out to meet three objectives: to evaluate the impact of COVID-19 on the sudents’ behavior; to clarify students’preparation at the start of the pandemic; to understand how they evaluate the changes forced by the pandemic. The results confirm the hypotheses: students’ behavior does not derive only from the negative emotional impact of COVID-19 but includes also positive motivational factors, such as the students’ degree of confidence and daily life reorientation. The authors recommend the adoption of educational innovative processes already being used, and future innovations, including artificial intelligence systems.